Niche-specific maize microbiomes enhance productivity and nitrogen uptake under intercropping - Chang, Yao; Wang, Jian; Xu, Chengbin; Qu, Fangying; Sun, Xuekai; Quan, Zhi; Yin, Liming; Fang, Yunting; Wang, Chao (Frontiers in Microbiology, 2026)
Intercropping is widely used to improve crop yield, but the microbial mechanisms driving biomass and nitrogen (N) gains remain unclear. In a maize-soybean intercropping system, we compared intercropped and monocultured maize to investigate niche-specific microbial processes. At the tasseling stage, bacterial and fungal communities were profiled across above- and belowground maize compartments and linked to organ-level biomass and N content. We found that intercropping significantly enhanced maize total biomass and nitrogen uptake, due to the greater increase in roots and leaves. The intercropping also restructured bacterial and fungal communities in a niche-specific manner: bacterial diversity declined in the phylloplane and root, leaf endospheres, whereas fungal diversity increased in the leaf endosphere and stem episphere. Moreover, higher bacterial diversity was associated with lower biomass and N content, while higher fungal diversity showed the opposite trend. Shifts in microbial composition, particularly enrichment of Proteobacteria, Bacteroidota, and Ascomycota, better predicted plant performance than diversity metrics alone. Overall, our findings suggest that intercropping enhances maize growth and N acquisition by steering niche-specific microbial assemblies, highlighting cross-compartment microbiome organization as a promising target for microbiome-informed crop management.